Analisis Yuridis Kedudukan Anak Hasil Penikahan Siri Berdasarkan BW Indonesia: Studi Putusan Nomor 282/Pdt/2016/PT SMG - Fajar Luthfi Annashrul; Edghar Abdullah Albab; Eka Sari Nurliana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Marriage is a relationship between two parties, namely the man and the woman. There are two types of marriage in Indonesia, namely legal marriage and unregistered marriage. This marriage that is not registered in the KUA is a hot issue in civil law, especially in the context of civil inheritance, where in the case of decision number 282 / PDT / 2016.PT. SMG, where there is a transfer of inheritance rights by the husband to the unregistered wife, then the legal wife sues the unregistered wife because it is considered not to have legal power or standing with decision number 282 / PDT / 2016.PT. SMG the legal wife wins in the lawsuit, thus the unregistered wife does not get an inheritance, therefore a study was made that can be studied using the normative method, a study that emphasizes the source of the writing comes from laws and literature reviews. This study aims to find out and examine the position of unregistered wives and legal wives in civil inheritance law and the legal status of unregistered wives in controlling inheritance in civil inheritance law.